Holland Dada - Schippers, K (Amsterdam : Em. Querido's uitgeverij, 1974)
van Rees, Otto ; van Rees Dutilh, A.C. ; Citroen, Paul ; van Doesburg, Theo ; van Doesburg, Nelly ; Schwitters, Kurt ; Rinsema, Evert ; Rinsema, Thijs ; Werkman, H.N.
Duits & Nederlands
boek
Keywords: Nederland